2009
DOI: 10.1086/644732
|View full text |Cite
|
Sign up to set email alerts
|

Topical Antimicrobial Therapy for Treating Chronic Wounds

Abstract: Various agents have been applied topically to treat infected wounds for millennia, but their proper role remains unclear. Topical therapy affords many potential advantages but also has disadvantages. Opinions differ on which clinical signs define wound infection and on whether quantitative microbiological studies are useful. Clinically infected wounds usually require systemic antibiotic therapy, whereas clinically uninfected wounds that are healing as expected do not require antimicrobials. There is controvers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
351
1
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(369 citation statements)
references
References 47 publications
1
351
1
16
Order By: Relevance
“…Iodophors are capable of percutaneous and mucous membrane absorption, and as a result should not be used in pregnant women, newborns, or patients with thyroid disorders. 16,17 In an ex vivo rat model, 10% povidone iodine ointment (Betadine) was shown to have a negative effect on microcirculation. 18 …”
Section: Povidone Iodinementioning
confidence: 99%
See 1 more Smart Citation
“…Iodophors are capable of percutaneous and mucous membrane absorption, and as a result should not be used in pregnant women, newborns, or patients with thyroid disorders. 16,17 In an ex vivo rat model, 10% povidone iodine ointment (Betadine) was shown to have a negative effect on microcirculation. 18 …”
Section: Povidone Iodinementioning
confidence: 99%
“…14 Antibiotics are often less cytotoxic than are antiseptics; however, they are more likely to lose their efficacy to bacterial resistance. 17 An additional known disadvantage of topical antibiotics is the occurrence of contact allergy. 13 Contact allergy is sometimes secondary to the antibiotic, but it is more often a reaction to preservatives in the delivery vehicle.…”
Section: Topical Antibioticsmentioning
confidence: 99%
“…Common bacterial strains found in chronic wounds are Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli, often residing in biofilms which are increasingly resistant to antimicrobial therapy (Lipsky & Hoey, 2009). Thus, antiseptic wound dressings and agents are becoming increasingly important in the management of chronic and infected wounds (Heyer et al, 2013;Lipsky & Hoey, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…4,5 New antibacterial agents with broad-spectrum impact against both Gram-positive 6 and Gram-negative 7 species, as well as against drug-resistant strains such as methicillinresistant Staphylococcus aureus 8 are needed for wound care and to treat topical and dermatological infections. 9 A chance observation in our laboratory revealed that creatinine (CRN; creatinine hydrochloride, CRN-HCl) halted the growth of bacteria on nutrient agar plates. CRN is the naturally occurring breakdown product of creatine phosphate, a high-energy molecule used to store and then donate, a high-energy phosphate to ADP for the synthesis of ATP in metabolism.…”
mentioning
confidence: 99%